1996
DOI: 10.1172/jci118670
|View full text |Cite
|
Sign up to set email alerts
|

Role of the D1A dopamine receptor in the pathogenesis of genetic hypertension.

Abstract: Since dopamine produced by the kidney is an intrarenal regulator of sodium transport, an abnormality of the dopaminergic system may be important in the pathogenesis of hypertension. In the spontaneously hypertensive rat (SHR), in spite of normal renal production of dopamine and receptor density, there is defective transduction of the D 1 receptor signal in renal proximal tubules, resulting in decreased inhibition of sodium transport (Na

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
172
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(177 citation statements)
references
References 37 publications
4
172
1
Order By: Relevance
“…The Dl receptors in the kidney are classified into D1A, a major Dl receptor expressed in the renal proximal tubule, and D1B subtypes. The blood pressure in mice lacking functional DlAreceptor is higher in homozygousand heterozygous mice than in normal controls, suggesting a causal relationship of the D 1A receptor gene with hypertension (48).…”
Section: Renal Dopamine Systemmentioning
confidence: 98%
“…The Dl receptors in the kidney are classified into D1A, a major Dl receptor expressed in the renal proximal tubule, and D1B subtypes. The blood pressure in mice lacking functional DlAreceptor is higher in homozygousand heterozygous mice than in normal controls, suggesting a causal relationship of the D 1A receptor gene with hypertension (48).…”
Section: Renal Dopamine Systemmentioning
confidence: 98%
“…23 It has been shown that the absence of DA codifying alleles is related to increases in systolic and diastolic pressure, thus suggesting a causal relation between the gene for the D 1A receptor and AHT. 24,25 Also, defects of coupling or activation of second messengers by this receptor (without affecting their distribution or quantity) are also related to the AHT appearance. 21 In this regard, the presence of polymorphic forms of the D 1 codifying gene has been described in patients with essential AHT.…”
Section: Role Of Dopamine In Kidney Functionmentioning
confidence: 99%
“…26 The D 5 /D 1 ratio in nephron is insignificant, therefore DA actions related to the D 1 (D 1 -like) family are normally attributed to D 1 . 24,27 As far as D 2 -like receptors are concerned, D 3 is expressed in proximal tubules and juxtaglomerular cells. It inhibits renin release by decreasing cAMP, as opposite to D 1 activation, which results in renin release.…”
Section: Role Of Dopamine In Kidney Functionmentioning
confidence: 99%
“…5 Impaired D 1A receptor function in the kidney has been reported in hypertensive animals, 6,7 as well as hypertensive humans, 8 possibly contributing to development of hypertension. 9 We have previously shown that there is reduced abundance and impaired G-protein coupling of cell surface D 1A receptors, resulting in inability of dopamine to inhibit sodium transporters in proximal tubules of insulin-resistant obese Zucker rats. 10 Interestingly, rosiglitazone treatment of obese rats corrected the decrease in cell surface D 1A receptor abundance 11 and the impairment in dopamine-induced inhibition of sodium transporters 11 in proximal tubules.…”
mentioning
confidence: 99%